PENATALAKSANAN ULTRASOUND TERAPI DAN WILLIAM FLEXION EXERCISE PADA SPONDYLOSIS LUMBALIS - Punuh, Naftali; Mamuaja, Filly (Lasalle Health Journal, 2024)
Introduction: Lumbar spondylosis is a degenerative condition of the lower spine, involving changes in the intervertebral discs, facet joints, and ligaments that cause pain, and occurs with age and is one of the causes of lower back pain that can ultimately cause obstacles in activities. Effective management in the form of integrated ultrasound therapy and William flexion exercise will allow patients to feel an increase in quality of life and better pain management, thereby increasing the patient's functional activity ability. Objective: Management of lumbar spondylosis with a combination of ultrasound therapy and William flexion exercise can provide more optimal results, which aim to reduce pain and increase the patient's functional activity. Method: This study is a case study / single case study pre-experiment with a one group pretest posttest design approach, which was conducted on a patient at R.W Monginsidi Hospital Teling Manado. Results: After the intervention of ultrasound therapy and William flexion exercise, changes in pain in the spine and increased functional activity were obtained. Conclusion: Ultrasound therapy and William flexion exercise management can reduce pain and increase functional activity in patients with lumbar spondylosis.